PENGENALAN STABILISASI TANAH DENGAN JET GROUTING - Indrastono Dwi Atmanto (TEKNIK, 2013)
Due to restriction of land availability it is frequently we have to build constructions on soft or low bearingcapacity soils, so that soil stabilization must be applied in order to increase its properties. There are manytechniques of soil stabilization, where its applicability depends on many factors regarding appropriateengineering judgement. This paper presents the soil stabilization method by jet grouting, including its theory andpractice.